A gel polymer electrolyte for a lithium metal battery with a wide temperature range and a preparation method thereof

CN123018119APending Publication Date: 2026-10-30HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611037374.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

本发明以宽温域稳定运行为核心目标,从正负极界面失效根源入手,采用自具分子级固有微孔的聚酰亚胺(PI-TB)构建正极适配层,通过顺序静电纺丝制备三层一体化不对称凝胶聚合物电解质,三层功能层的精准设计与自具微孔聚酰亚胺的材料创新,解决了现有不对称电解质高温界面副反应剧烈、低温离子传输动力学差、层间界面阻抗随温度波动劣化的问题,实现锂金属电池在-30℃~70℃宽温域范围内的稳定循环与安全运行

Benefits of technology

[0018](1)不对称界面精准设计,协同解决宽温域两极界面失效难题:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018119A_ABST
    Figure CN123018119A_ABST
Patent Text Reader

Abstract

The application discloses a kind of gel polymer electrolyte for wide temperature range lithium metal battery and preparation method thereof, the electrolyte is three-layer integration asymmetric structure, from negative electrode side to positive electrode side in proper order is negative electrode adaptation layer, intermediate transition layer and positive electrode adaptation layer, wherein: the negative electrode adaptation layer is PEO / PVDF-HFP composite polymer matrix loaded with inorganic ceramic filler;The intermediate transition layer is pure PVDF-HFP polymer matrix;The positive electrode adaptation layer is self-microporous polyimide PI-TB / PVDF-HFP composite polymer matrix loaded with inorganic ceramic filler.Three-layer structure is integrally formed by sequential electrospinning process, fiber is overlapped and entangled with each other, there is no obvious macroscopic interfacial interface, gel state is formed after electrolyte is fully infiltrated, realize the stable circulation and safe operation of lithium metal battery in-30℃~70℃ wide temperature range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium metal battery electrolyte technology, and relates to a gel polymer electrolyte and its preparation method, specifically to an asymmetric self-microporous polyimide-based gel polymer electrolyte for wide-temperature-range lithium metal batteries and its preparation method. Background Technology

[0002] With the rapid development of new energy vehicles and large-scale energy storage, higher requirements are being placed on the energy density, cycle life, and environmental adaptability of lithium batteries. Lithium metal anodes, with their extremely high theoretical specific capacity (3860 mAh / g) and extremely low redox potential, are considered the core anode material for next-generation high-energy-density batteries. However, lithium metal anodes are highly active and prone to lithium dendrite growth, and high-voltage ternary cathodes are susceptible to transition metal dissolution and electrolyte oxidative decomposition, resulting in poor battery interface stability and short cycle life. Under extreme temperature conditions, low temperatures cause a sharp increase in interface impedance and deterioration of ion transport kinetics, while high temperatures exacerbate interface side reactions and structural failure, ultimately leading to particularly severe battery performance degradation below -30°C and above 70°C.

[0003] Gel polymer electrolytes (GPEs) combine the high ionic conductivity of liquid electrolytes with the flexibility and safety of polymer matrices, making them an important electrolyte system for lithium metal batteries. However, traditional homogeneous GPEs struggle to simultaneously accommodate both highly active lithium anodes and high-voltage cathodes, and are ill-suited for wide-temperature operating conditions: the lithium-ion flux cannot be uniformly controlled on the anode side, leading to high lithium deposition overpotential and soaring interfacial impedance at low temperatures, while at high temperatures, lithium dendrites and repeated SEI fracture are easily induced; on the cathode side, oxidation resistance is insufficient, side reactions intensify at high temperatures, and ion transport kinetics are slow at low temperatures. To address these issues, asymmetric GPE structures have been proposed, employing different functional polymer matrices on the anode and cathode sides to meet the interfacial requirements of each electrode. However, existing designs lack precise optimization for interfacial failures across a wide temperature range, resulting in insufficient wide-temperature adaptability.

[0004] Existing asymmetric electrolytes often use polyacrylonitrile (PAN) as the positive electrode matrix, leveraging its oxidation resistance to adapt to high-voltage cathodes; and polyethylene oxide (PEO) composite polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) as the negative electrode matrix to regulate lithium deposition behavior. However, the PAN matrix has significant wide-temperature adaptability drawbacks: poor dimensional stability and susceptibility to thermal shrinkage at high temperatures, leading to the risk of internal short circuits in the battery; and weak chain segment mobility and slow ion transport kinetics at low temperatures, resulting in a sharp increase in polarization at the positive electrode interface, severely limiting the wide-temperature range application of the battery. Meanwhile, traditional bilayer electrolytes are mostly prepared by direct stacking and hot-press coating, resulting in a clear macroscopic interface between the two heteropolymer layers. This not only leads to high interfacial impedance at room temperature but also causes a sharp increase in interfacial impedance at low temperatures and deterioration of interlayer delamination at high temperatures, disrupting the continuity of ion transport across the entire temperature range.

[0005] Polyimide (PI) possesses excellent thermal stability, mechanical strength, and oxidation resistance, theoretically making it a viable alternative to PAN as a high-voltage cathode substrate. However, conventional polyimide electrolytes prepared by traditional casting methods have a dense membrane structure with tightly packed molecular chains, extremely low inherent porosity, and poor electrolyte adsorption and retention capabilities. Furthermore, the rigidity of the polyimide backbone severely restricts chain segment movement at low temperatures, resulting in low ionic conductivity and failing to meet the requirements for wide-temperature-range applications. Microporous polyimide (PI-TB), by introducing rigidly twisted Tröger's base structures into the backbone, can form permanent molecular-level micropores between polymer molecular chains. This enhances the electrolyte adsorption capacity of the substrate without the need for additional pore-forming, while the rigid framework ensures structural stability at high temperatures, potentially overcoming the low-temperature ion transport bottleneck of ordinary polyimides. Currently, microporous polyimide is primarily used in gas separation and proton exchange membranes; there are no reports on its application in lithium metal battery asymmetric gel electrolytes or in the construction of wide-temperature-range integrated electrolytes using sequential electrospinning processes. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a gel polymer electrolyte for wide-temperature-range lithium metal batteries and its preparation method. With stable operation over a wide temperature range as its core objective, this invention addresses the root causes of interface failure between the positive and negative electrodes. It utilizes polyimide (PI-TB) with inherent molecular-level micropores to construct the positive electrode adapter layer, and then prepares a three-layer integrated asymmetric gel polymer electrolyte through sequential electrospinning. The precise design of the three functional layers and the innovative material of the microporous polyimide solve the problems of severe high-temperature interface side reactions, poor low-temperature ion transport kinetics, and deterioration of interlayer interface impedance with temperature fluctuations in existing asymmetric electrolytes. This enables stable cycling and safe operation of lithium metal batteries within a wide temperature range of -30℃ to 70℃.

[0007] The objective of this invention is achieved through the following technical solution:

[0008] A gel polymer electrolyte for wide-temperature-range lithium metal batteries has a three-layer integrated asymmetric structure, consisting of a negative electrode adapter layer, an intermediate transition layer, and a positive electrode adapter layer, arranged sequentially from the negative electrode side to the positive electrode side.

[0009] The negative electrode adapter layer is a PEO / PVDF-HFP composite polymer matrix loaded with inorganic ceramic filler, wherein the mass ratio of PEO to PVDF-HFP is 3:7 to 7:3, and the loading of inorganic ceramic filler is 5 to 20 wt% of the total mass of PEO and PVDF-HFP.

[0010] The intermediate transition layer is a pure PVDF-HFP polymer matrix;

[0011] The positive electrode adapter layer is a microporous polyimide PI-TB / PVDF-HFP composite polymer matrix loaded with inorganic ceramic filler. The mass ratio of microporous polyimide to PVDF-HFP is 1:9 to 5:5, and the loading of inorganic ceramic filler is 5 to 20 wt% of the total mass of microporous polyimide and PVDF-HFP.

[0012] A method for preparing the above-mentioned wide-temperature-range lithium metal battery gel polymer electrolyte includes the following steps:

[0013] Step 1: Prepare electrospinning precursor solutions: Prepare spinning solutions for the negative electrode layer, intermediate layer, and positive electrode layer respectively.

[0014] Step 2: Prepare an integrated asymmetric polymer membrane using sequential electrospinning: Spin the positive electrode adapter layer, intermediate transition layer, and negative electrode adapter layer sequentially on the same receiving substrate. Through continuous spinning, the three layers of fibers are interlocked and integrally formed to obtain the asymmetric polymer precursor membrane.

[0015] Step 3: Post-treatment and electrolyte wetting of the precursor membrane: The precursor membrane is placed in a vacuum oven and dried by step heating to completely remove the organic solvent; then, in an argon-protected glove box, the dried membrane is immersed in the electrolyte for full wetting, and after removal, excess electrolyte on the surface is absorbed to obtain an asymmetric self-porous polyimide-based gel polymer electrolyte.

[0016] The application of the above-mentioned asymmetric self-porous polyimide-based gel polymer electrolyte in a wide-temperature-range lithium metal battery, wherein the lithium metal battery includes the above-mentioned asymmetric self-porous polyimide-based gel polymer electrolyte, the negative electrode is a lithium metal negative electrode, and the positive electrode is a high-voltage ternary positive electrode material.

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] (1) Precise design of asymmetric interfaces to collaboratively solve the problem of failure at polar interfaces over a wide temperature range:

[0019] To address the differentiated interface failure mechanisms of positive and negative electrodes under wide temperature conditions, a three-layer structure achieves precise adaptation: On the negative electrode side, the PEO / PVDF-HFP composite matrix reduces lithium nucleation overpotential and interface impedance at low temperatures through the coordination of lithium ions with ether bonds and the synergistic effect of LLZTO promoting lithium salt dissociation; at high temperatures, it homogenizes lithium ion flux, induces the formation of a dense and stable SEI film, and inhibits lithium dendrite growth and repeated SEI breakage. On the positive electrode side, the microporous polyimide composite PVDF-HFP provides abundant ion transport sites at low temperatures due to its inherent molecular-level micropores, alleviating the problem of weak chain segment movement in ordinary polymers at low temperatures; at high temperatures, it leverages the excellent oxidation resistance and mechanical strength of PI, adapting to high-voltage positive electrodes above 4.3 V. Simultaneously, the nitrogen-containing groups in PI can coordinate with transition metal ions, effectively inhibiting transition metal dissolution and electrolyte oxidative decomposition. The intermediate pure PVDF-HFP transition layer eliminates the macroscopic interface of the heterolayer, avoiding a sudden increase in interface impedance at low temperatures and interlayer delamination at high temperatures, constructing a continuous lithium-ion transport channel across the entire temperature range.

[0020] (2) Innovation of microporous polyimide materials, breaking through the bottleneck of wide-temperature application of ordinary polyimides:

[0021] This innovative approach introduces microporous polyimide into the positive electrode side of a gel electrolyte. The inherent molecular-level micropores formed by the rigid twisted structure of its main chain provide more active sites for lithium-ion transport without the need for additional pore-forming, lowering the ion migration energy barrier and significantly improving ion transport kinetics at low temperatures. This breakthrough addresses the bottleneck of low low-temperature ionic conductivity in ordinary dense polyimides at the material level. Simultaneously, the polyimide itself possesses excellent thermal stability and mechanical strength, solving the problems of high-temperature shrinkage and poor dimensional stability of traditional PAN matrices, enabling stable operation of the electrolyte across a wide temperature range of -30℃ to 70℃.

[0022] (3) Sequential electrospinning integral molding ensures the stability of the interlayer structure across the entire temperature range:

[0023] A three-layer structure is prepared by continuous sequential electrospinning, with interlayer fibers interpenetrating and overlapping, and no obvious interlayer delamination interface. Compared with the bilayer electrolyte prepared by traditional coating and hot pressing, the interlayer bonding force is stronger, the interfacial impedance is lower, and the overall mechanical properties are better. The three-dimensional fiber network formed by electrospinning can ensure electrolyte storage and interfacial contact, and provide a basic pathway for ion transport.

[0024] (4) LLZTO packing synergistic effect optimizes ion transport and structural stability across the entire temperature range:

[0025] Introducing LLZTO solid electrolyte nanofiller into the positive and negative electrode functional layers can, on the one hand, adsorb LiPF6 anions through Lewis acid-base interaction, promote lithium salt dissociation, and significantly improve lithium ion transference number and ionic conductivity across the entire temperature range, especially alleviating the problem of insufficient lithium salt dissociation at low temperatures; on the other hand, it can further improve the mechanical strength and thermal dimensional stability of the electrolyte membrane, suppress membrane shrinkage and deformation at high temperatures, and improve the safety performance of the battery during wide-temperature operation.

[0026] (5) The process is simple and controllable, and has strong industrial adaptability.

[0027] The preparation process of this invention is simple, the parameters are controllable, no complex equipment is required, and it can be adapted to the existing industrial preparation process of lithium batteries. The prepared electrolyte can be directly applied to lithium metal batteries and high-voltage ternary battery systems, significantly improving the cycle life and rate performance of batteries in a wide temperature range of -30℃ to 70℃, and has good prospects for industrial application. Attached Figure Description

[0028] Figure 1 This is a schematic cross-sectional view of the three-layer electrolyte structure;

[0029] Figure 2 Schematic diagram of PI-TB / PVDF-HFP composite fiber and intrinsic microporous lithium-ion transport;

[0030] Figure 3 This is a flowchart illustrating the preparation process of the three-layer asymmetric gel polymer electrolyte of the present invention. Detailed Implementation

[0031] The technical solution of the present invention will be further described below with reference to the accompanying drawings, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention that do not depart from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention.

[0032] This invention provides a gel polymer electrolyte for wide-temperature-range lithium metal batteries, such as... Figure 1 and Figure 2 As shown, the electrolyte is a three-layer integrated asymmetric structure adapted for operation in a wide temperature range of -30℃ to 70℃. From the negative electrode side to the positive electrode side, it consists of a negative electrode adapter layer, an intermediate transition layer, and a positive electrode adapter layer. The three-layer structure is integrally formed by sequential electrospinning, with fibers overlapping and entangled, without obvious macroscopic interlayer interfaces. After being fully wetted by the electrolyte, it forms a gel state, allowing lithium ions to be continuously and stably transported within the three-layer structure.

[0033] The negative electrode adapter layer is a PEO / PVDF-HFP composite polymer matrix loaded with inorganic ceramic filler. It is designed to address the negative electrode interface failure problem in a wide temperature range: at low temperatures, the coordination of lithium ions with ether bonds and inorganic filler promotes lithium salt dissociation, reduces lithium nucleation overpotential, and alleviates the low-temperature interface impedance spike; at high temperatures, it homogenizes lithium ion flux, induces the formation of a dense and stable SEI film, and inhibits lithium dendrite growth and interface side reactions; the mass ratio of PEO to PVDF-HFP is 3:7~7:3, preferably 4:6~6:4.

[0034] The intermediate transition layer is a pure PVDF-HFP polymer matrix, which is used to eliminate the macroscopic interface of heterogeneous functional layers in the entire temperature range, construct a continuous lithium-ion transport channel, avoid the sudden increase of interface impedance at low temperature and the deterioration of interlayer peeling at high temperature, and ensure the continuity and stability of ion transport in the entire temperature range.

[0035] The positive electrode adapter layer is a microporous polyimide PI-TB / PVDF-HFP composite polymer matrix loaded with inorganic ceramic filler. It is designed to address the problem of positive electrode interface failure over a wide temperature range: at low temperatures, it relies on the inherent molecular-level micropores of PI-TB to provide a continuous ion transport path, compensating for the weak chain segment movement of ordinary polyimide at low temperatures and reducing the charge transfer impedance at the positive electrode interface; at high temperatures, it leverages the intrinsic oxidation resistance and thermal stability of polyimide, combined with the coordination effect of nitrogen-containing groups on transition metals, to inhibit the oxidative decomposition of electrolyte and the dissolution of transition metals; the mass ratio of microporous polyimide to PVDF-HFP is 1:9~5:5, preferably 2:8~4:6;

[0036] The microporous polyimide described is an aromatic polyimide with a main chain containing a Choger base structure. It forms inherent micropores at the molecular level through a rigid twisted structure of the main chain, and its BET specific surface area is 300~800 m². 2 / g, with pore size distribution between 0.5 and 2nm;

[0037] The inorganic ceramic filler is tantalum-doped lithium lanthanum zirconate (Li). 6.4 La3Zr 1.4 Ta 0.6 O 12 LLZTO nanoparticles with a particle size of 50~200 nm are used, and the filler accounts for 5~20% of the mass of both the negative electrode adapter layer and the positive electrode adapter layer, preferably 10wt%.

[0038] The total thickness of the electrolyte is 20~100 μm, the thickness of the negative electrode adapter layer is 5~30 μm, the thickness of the intermediate transition layer is 2~10 μm, and the thickness of the positive electrode adapter layer is 10~50 μm.

[0039] The electrolyte is a carbonate-based electrolyte, in which the solute is lithium hexafluorophosphate (LiPF6) with a concentration of 1~1.5 mol / L; and the solvent is one or more of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) mixed in any proportion.

[0040] This invention also provides a method for preparing the above-mentioned gel polymer electrolyte for wide-temperature-range lithium metal batteries, such as... Figure 3 As shown, the method specifically includes the following steps:

[0041] Step 1: Preparation of self-contained microporous polyimide (PI-TB): Using aromatic dianhydrides and diamines as raw materials, self-contained microporous polyimide with rigid twisted Choger bases in the main chain is prepared through Choger base construction reaction and imidization reaction.

[0042] Step 2: Prepare electrospinning precursor solutions: Prepare spinning solutions for the negative electrode layer, intermediate layer, and positive electrode layer respectively.

[0043] In this step, the spinning solution of the negative electrode layer is prepared as follows: PEO and PVDF-HFP are added to an organic solvent in proportion, heated and stirred until completely dissolved, then LLZTO nanoparticles are added and ultrasonically dispersed until uniform, to obtain a spinning solution with a solid content of 8~15%.

[0044] In this step, the intermediate layer spinning solution is prepared by adding PVDF-HFP to an organic solvent and stirring until completely dissolved to obtain a spinning solution with a solid content of 8-12%.

[0045] In this step, the positive electrode layer spinning solution is prepared as follows: PI-TB and PVDF-HFP are added to an organic solvent in a certain proportion, heated and stirred until completely dissolved, then LLZTO nanoparticles are added and ultrasonically dispersed until uniform, to obtain a spinning solution with a solid content of 8~15%.

[0046] In this step, the organic solvent is one or a mixture of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP).

[0047] Step 3: Prepare an integrated asymmetric polymer membrane using sequential electrospinning: Spin the positive electrode adapter layer, intermediate transition layer, and negative electrode adapter layer sequentially on the same receiving substrate. Through continuous spinning, the three layers of fibers overlap and are integrally formed to obtain the asymmetric polymer precursor membrane.

[0048] In this step, the parameters of the electrospinning process are as follows: spinning voltage is 10~25 kV, receiving distance is 10~20 cm, feed rate is 0.5~2 mL / h, ambient temperature is 25~40℃, and relative humidity is 30%~60%.

[0049] Step 4: Post-treatment and electrolyte wetting of the precursor membrane: The precursor membrane is placed in a vacuum oven and dried by step heating to completely remove the organic solvent; then, in an argon-protected glove box, the dried membrane is immersed in the electrolyte for full wetting, and after removal, excess electrolyte on the surface is absorbed to obtain an asymmetric self-porous polyimide-based gel polymer electrolyte.

[0050] In this step, the specific conditions for the stepped heating vacuum drying are as follows: first, vacuum dry at 40~60℃ for 10~14 h, then heat up to 80~100℃ and vacuum dry for 4~8 h.

[0051] In this step, the electrolyte soaking time is 10~14 h, and the soaking temperature is 25℃.

[0052] The present invention also provides a wide temperature range lithium metal battery, the lithium metal battery comprising the above-mentioned asymmetric self-porous polyimide-based gel polymer electrolyte, wherein the negative electrode of the lithium metal battery is a lithium metal negative electrode and the positive electrode is a high-voltage ternary positive electrode material.

[0053] Example 1

[0054] This embodiment provides a method for preparing an asymmetric, self-porous polyimide-based gel polymer electrolyte. The specific preparation steps of the method are as follows:

[0055] Step 1: Synthesis of self-porous polyimide (PI-TB).

[0056] Preparation of imide-containing cyclic diamine monomer: 1.3409 g of 1,4,5,8-naphthalenetetracarboxylic dianhydride (NTCDA) was added to a three-necked flask containing 23 mL of N-methylpyrrolidone (NMP), and stirred at room temperature under nitrogen protection until completely dissolved. 1.3620 g of 2,5-dimethyl-p-phenylenediamine (DPD) was added, and the mixture was heated to 80 °C and held at this temperature for 12 h to complete the amidation process. 32 mL of toluene was added to the reaction system as an azeotropic dehydrating agent, and the temperature was further increased to 180 °C under nitrogen protection, and the mixture was refluxed under azeotropic conditions for 9 h to remove the water generated in the reaction, completing the imide ring closure. After the reaction, the mixture was cooled to room temperature, and the reaction solution was poured into deionized water to precipitate the solid. After filtration, the solid was dried under vacuum at 80 °C. The solid was then washed with an ethanol / water mixture until the filtrate was clear, purified by reflux with ethanol at 90 °C for 9 h, filtered, and dried under vacuum at 80 °C for 6 h to obtain a bright red imide-containing cyclic diamine monomer powder.

[0057] Choger base construction and polymerization: 4.5410 g of the above-mentioned imide-containing cyclic diamine monomer and 0.1080 g of m-phenylenediamine (MPD) were added to a reaction flask, and 30 mL of trifluoroacetic acid was rapidly added dropwise. The mixture was stirred for 30 min until the solid was completely dissolved. 5.8 mL of dimethoxymethane (DMM) was slowly added dropwise, and the reaction temperature was controlled at -5 ℃. The reaction was maintained at this temperature for 48 h. After the reaction was completed, the reaction solution was slowly poured into dilute alkaline water to precipitate the polymer. The polymer was washed 2-3 times with deionized water. The polymer was purified by reflux with methanol at 80 ℃ for 7 h and then dried under vacuum at 120 ℃ for 4 h to obtain a brown fibrous polyimide product with its own microporous structure (PI-TB).

[0058] Step 2: Preparation of electrospinning precursor solution.

[0059] Negative electrode layer spinning solution: PEO and PVDF-HFP were added to DMF solvent at a mass ratio of 1:1 and stirred at 40°C until completely dissolved; then LLZTO nanoparticles (average particle size 100 nm) accounting for 10% of the total polymer mass were added and ultrasonically dispersed for 30 min to obtain a uniform spinning solution with a solid content of 10 wt%.

[0060] Intermediate layer spinning solution: PVDF-HFP is added to DMF solvent and stirred at room temperature until completely dissolved to obtain a spinning solution with a solid content of 10 wt%.

[0061] Positive electrode layer spinning solution: PI-TB and PVDF-HFP were added to DMF solvent at a mass ratio of 3:7 and stirred at 40°C until completely dissolved; then LLZTO nanoparticles accounting for 10% of the total polymer mass were added and ultrasonically dispersed for 30 min to obtain a uniform spinning solution with a solid content of 10wt%.

[0062] Step 3: Prepare an integrated membrane by sequential electrospinning.

[0063] A horizontal electrospinning machine is used, with aluminum foil as the receiving substrate, to perform three-layer spinning sequentially:

[0064] First, spin the positive electrode adapter layer: the spinning voltage is 18 kV, the receiving distance is 15 cm, the feed rate is 1 mL / h, and the spinning time is 2h, to obtain a positive electrode fiber membrane with a thickness of about 20 μm.

[0065] Without changing the receiving substrate, the intermediate layer spinning solution was directly replaced, the spinning voltage was adjusted to 16 kV, the receiving distance to 15 cm, the feed rate to 0.8 mL / h, and the spinning time to 30 min, and an intermediate transition layer with a thickness of about 5 μm was grown in situ on the surface of the positive electrode layer.

[0066] The spinning solution for the negative electrode layer was replaced, and the spinning voltage was adjusted to 17 kV, the receiving distance to 15 cm, the feed rate to 1 mL / h, and the spinning time to 1.5 h, forming a negative electrode adapter layer with a thickness of approximately 15 μm on the surface of the intermediate layer. Finally, a three-layer integrated asymmetric polymer precursor film with a total thickness of approximately 40 μm was obtained.

[0067] Step 4: Post-treatment and electrolyte wetting.

[0068] The precursor membrane was peeled off from the aluminum foil and placed in a vacuum oven to dry at 60°C for 12 h and then at 80°C for 6 h to completely remove residual solvent. Subsequently, in an argon glove box (water and oxygen content < 0.1 ppm), the dried membrane was immersed in a 1 mol / L LiPF6EC / DMC / EMC (volume ratio 1:1:1) electrolyte at 25°C for 12 h. After removal, excess electrolyte on the surface was gently blotted with filter paper to obtain an asymmetric self-porous polyimide-based gel polymer electrolyte.

[0069] Example 2

[0070] The difference between this embodiment and Embodiment 1 is that the mass ratio of PI-TB to PVDF-HFP in the positive electrode spinning solution is 2:8.

[0071] Example 3

[0072] The difference between this embodiment and Embodiment 1 is that the mass ratio of PI-TB to PVDF-HFP in the positive electrode spinning solution is 4:6.

[0073] Example 4

[0074] The difference between this embodiment and embodiments 1-3 is that the mass percentage of LLZTO filler in both the positive and negative electrode layers is 5%.

[0075] Example 5

[0076] The difference between this embodiment and embodiments 1-3 is that the mass percentage of LLZTO filler in both the positive and negative electrode layers is 15%.

Claims

1. A gel polymer electrolyte for wide-temperature-range lithium metal batteries, characterized in that... The electrolyte has a three-layer integrated asymmetric structure, consisting of a negative electrode adapter layer, an intermediate transition layer, and a positive electrode adapter layer, arranged sequentially from the negative electrode side to the positive electrode side. The negative electrode adapter layer is a PEO / PVDF-HFP composite polymer matrix loaded with inorganic ceramic filler, wherein the mass ratio of PEO to PVDF-HFP is 3:7 to 7:3, and the loading of inorganic ceramic filler is 5 to 20 wt% of the total mass of PEO and PVDF-HFP. The intermediate transition layer is a pure PVDF-HFP polymer matrix; The positive electrode adapter layer is a microporous polyimide PI-TB / PVDF-HFP composite polymer matrix loaded with inorganic ceramic filler. The mass ratio of microporous polyimide to PVDF-HFP is 1:9 to 5:5, and the loading of inorganic ceramic filler is 5 to 20 wt% of the total mass of microporous polyimide and PVDF-HFP.

2. The gel polymer electrolyte for wide-temperature-range lithium metal batteries according to claim 1, characterized in that... The mass ratio of PEO to PVDF-HFP is 4:6 to 6:4; the mass ratio of self-microporous polyimide to PVDF-HFP is 2:8 to 4:6; in the negative electrode adapter layer, the inorganic ceramic filler loading is 10wt% of the total mass of PEO and PVDF-HFP; in the positive electrode adapter layer, the inorganic ceramic filler loading is 10wt% of the total mass of self-microporous polyimide and PVDF-HFP.

3. The gel polymer electrolyte for wide-temperature-range lithium metal batteries according to claim 1 or 2, characterized in that... The aromatic polyimide with microporous structure as its main chain and containing Choger bases has a BET specific surface area of ​​300~800 m². 2 / g, with a pore size distribution between 0.5 and 2 nm; the inorganic ceramic filler is tantalum-doped lithium lanthanum zirconate nanoparticles with a particle size of 50 to 200 nm.

4. The gel polymer electrolyte for wide-temperature-range lithium metal batteries according to claim 1, characterized in that... The total thickness of the electrolyte is 20~100 μm, the thickness of the negative electrode adapter layer is 5~30 μm, the thickness of the intermediate transition layer is 2~10 μm, and the thickness of the positive electrode adapter layer is 10~50 μm.

5. A method for preparing a gel polymer electrolyte for a wide-temperature-range lithium metal battery according to any one of claims 1-4, characterized in that... The method includes the following steps: Step 1: Prepare electrospinning precursor solutions: Prepare spinning solutions for the negative electrode layer, intermediate layer, and positive electrode layer respectively. Step 2: Prepare an integrated asymmetric polymer membrane using sequential electrospinning: Spin the positive electrode adapter layer, intermediate transition layer, and negative electrode adapter layer sequentially on the same receiving substrate. Through continuous spinning, the three layers of fibers are interlocked and integrally formed to obtain the asymmetric polymer precursor membrane. Step 3: Post-treatment and electrolyte wetting of the precursor membrane: Place the precursor membrane in a vacuum oven and dry it by step heating to completely remove the organic solvent. Subsequently, in an argon-protected glove box, the dried membrane was immersed in the electrolyte for full wetting. After removal, excess electrolyte on the surface was absorbed to obtain an asymmetric self-porous polyimide-based gel polymer electrolyte.

6. The method for preparing a gel polymer electrolyte for a wide-temperature-range lithium metal battery according to claim 5, characterized in that... The electrolyte is a carbonate-based electrolyte.

7. The method for preparing a gel polymer electrolyte for wide-temperature-range lithium metal batteries according to claim 6, characterized in that... The electrolyte contains lithium hexafluorophosphate as the solute at a concentration of 1-1.5 mol / L, and one or more of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate as the solvent.

8. The method for preparing a gel polymer electrolyte for wide-temperature-range lithium metal batteries according to claim 5, characterized in that... The parameters of the electrospinning process are as follows: spinning voltage is 10~25 kV, receiving distance is 10~20 cm, feed rate is 0.5~2 mL / h, ambient temperature is 25~40℃, and relative humidity is 30%~60%; the specific conditions for the stepped heating vacuum drying are: first vacuum drying at 40~60℃ for 10~14 h, then heating to 80~100℃ for vacuum drying for 4~8 h.

9. The application of a gel polymer electrolyte for a wide-temperature-range lithium metal battery as described in any one of claims 1-4 in a wide-temperature-range lithium metal battery.

10. The application of the gel polymer electrolyte for wide-temperature-range lithium metal batteries according to claim 9 in wide-temperature-range lithium metal batteries, characterized in that... The lithium metal battery comprises an asymmetric self-porous polyimide-based gel polymer electrolyte, a lithium metal negative electrode, and a high-voltage ternary positive electrode material.